In vitro antagonism of Trichoderma and naturally occurring fungi from elms against Ophiostoma novo‐ulmi. Issue 1 (7th August 2012) - Díaz, G.; Córcoles, A. I.; Asencio, A. D.; Torres, M. P.; Kim, M‐S.
Summary The antagonist ability of four fungal endophytes isolated from elms (Trichoderma atroviride GF13, Diaporthe eres GF2, Diplodia ulmi GF5 and Alternaria alternata GF6) and two fungi from a collection (Trichoderma harzianum and Trichoderma virens) was evaluated against six strains of Ophiostoma novo‐ulmi (1, 10, 19, 32, 43 and O‐Va), the causal agent of Dutch elm disease. Dual culture tests were established in PDA and MA culture media to test the interactions between pathogenic fungi and potential antagonist ones. The fungi showed varying levels of antagonist capacity against O. novo‐ulmi. Among them, T. atroviride and T. harzianum had the greatest inhibiting effect (around 50%). Culture filtrates and previously inoculated cellophane discs from T. harzianum and T. atroviride also caused growth inhibition of O. novo‐ulmi, with less intensity in strains 10 and 19. The control mechanisms involved in the process were competition, mycoparasitism and the production of soluble and diffusible antifungal metabolites. The new isolate T. atroviride GF13 was efficient as antagonist. It showed antagonist ability against non‐elm‐derived fungi such as Verticillium, Fusarium, Aspergillus, Rhizopus and Penicillium. These results suggest interesting application possibilities in the biological control of Dutch elm disease.